THE EFFICACY AND SAFETY OF IMMARD (HYDROXYCHLOROQUINE) IN RHEUMATOID ARTHRITIS ACCORDING TO THE DATA OF AN OPEN-LABEL UNCONTROLLED TRIAL IN OUTPATIENT PRACTICE - Rimma Mikhailovna Balabanova; D A Gukasyan; E L Shakhramanova; D V Goryachev (Научно-практическая ревматология, 2012)
Objective: to evaluate the efficacy and safety of immard in rheumatoid arthritis (RA) in outpatient practice. Subjects and methods. The open-labeled uncontrolled trial enrolled 30 patients with the reliable and valid diagnosis of RA of varying duration. Immard was used in patients with early RA or as an additive agent when a disease-modifying anti-rheumatic drug (mainly methotrexate) was ineffective. The effect of immard was evaluated 3 months of its intake of 400 mg from the number of swollen and tender joints, patients' and physicians' total ratings of disease activity on a visual analogue scale, from ESR values, C-reactive protein (CRP) levels, and DAS28 scores. Results. There was a significant decrease in the number of swollen joints and DAS28 scores in the patients receiving a combination of methotrexate and immard. No significant reduction in ERS and CRP levels was revealed during the follow-up period.